2014
DOI: 10.1080/15459624.2014.890286
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Firefighters to Particulates and Polycyclic Aromatic Hydrocarbons

Abstract: Firefighting continues to be among the most hazardous yet least studied occupations in terms of exposures and their relationship to occupational disease. Exposures are complex, involving mixtures of particles and chemicals such as polycyclic aromatic hydrocarbons (PAHs). Adverse health effects associated with these agents include elevated incidences of coronary heart disease and several cancers. PAHs have been detected at fire scenes, and in the firehouse rest area and kitchen, routinely adjoining the truck ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
79
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(89 citation statements)
references
References 18 publications
5
79
2
3
Order By: Relevance
“…It was also reported that Zn, Pb in PM 2.5 can lead to heart rate and blood pressure increase (Cakmak et al, 2014). In addition, PAHs are also suggested to be associated with CVD (Baxter et al, 2014). It has been reported that PM 2.5 with a small size can penetrate deeply into the alveolar regions of the lung and even transmit through blood into the circulation, including the heart, and then triggers cardiovascular effects (Guarnieri and Balmes, 2014;Sancini et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that Zn, Pb in PM 2.5 can lead to heart rate and blood pressure increase (Cakmak et al, 2014). In addition, PAHs are also suggested to be associated with CVD (Baxter et al, 2014). It has been reported that PM 2.5 with a small size can penetrate deeply into the alveolar regions of the lung and even transmit through blood into the circulation, including the heart, and then triggers cardiovascular effects (Guarnieri and Balmes, 2014;Sancini et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Taiyuan winter PM 2.5 is characterized by the presences of nitrate, sulfite, organic carbon fraction, PAHs, and elements such as Hg, As, Pb, and Zn and others [14,15,23]. As for PAHs and the transition metals such as Zn, they have been demonstrated to be associated with cardiac injury and heart disease [52,53]. Additionally, sulfate and nitrate in PM may indirectly affect health through interactions with certain metal species and with production of secondary organic matter [54].…”
Section: Discussionmentioning
confidence: 99%
“…Smoke emitted by a fire contains carcinogens [11][12][13][14][15]. From among the polycyclic aromatic hydrocarbons (PAHs) released into the air in vast amounts during a fire, are benzo[a]pyrene, which is carcinogenic to humans, dibenz [a,h] [16,17].…”
Section: Introductionmentioning
confidence: 99%